The Effect of Ferrous Nano-oxide Particles on Physiological Traits and Nutritional Compounds of Soybean ( Glycine max L.) Seed - ROGHAYYEH SHEYKHBAGLOU; MOHAMMAD SEDGHI; BAHRAM FATHI-ACHACHLOUIE (Anais da Academia Brasileira de Ciências, 2018)
ABSTRACT Soybean (Glycine max L.) seed contains amounts of protein, lipid, carbohydrate and mineral elements, which protein and lipid have been known as a main part for soybean’s trade value. In this study, in order to investigate the effect of ferrous nano-oxide particles on nutritional compounds of soybean seed, an experiment with 5 treatments and 3 replications was conducted as a randomized complete block design. Treatments were 5 concentrations of ferrous nano-oxide particles including 0, 0.25, 0.5, 0.75 and 1 g L-1 which were sprayed 3 times at 4 and 8 leaves stage and pod initiation. Lipid and protein contents, fatty acids profile, some of mineral elements such as Fe, Mg, Ca and P, chlorophyll a, b and total chlorophyll content were determined. Results showed that solution containing ferrous nano-oxide particles had significant effect on nutritional compounds of soybean seed (P<0.01) compared to control. The highest content of lipid and protein (25.4 and %33.8, respectively) observed by applying 0.75 g L-1 of ferrous nano-oxide and the lowest content was also in control. Changes in the trends of fatty acids profile (palmitic, oleic, linoleic and linolenic acids), some of mineral elements (Fe, Mg, Ca and P) and chlorophyll contents were similar to lipid and protein levels which by increasing in concentration of ferrous nano-oxide from 0 to 0.75 g L-1 all measured parameters also increased, but reduction in all parameters was observed in concentration from 0.75 to 1 g L-1. In conclusion, application of 0.75 to 1 g L-1 ferrous nano-oxide had the best effect on the nutrient composition of soybean seed.